A porous media model for CFD simulations of gas-liquid two-phase flow in rotating packed beds. (2nd November 2018) - Lu, X.; Xie, P.; Ingham, D.B.; Ma, L.; Pourkashanian, M.
Highlights: A new porous media model is proposed for an Eulerian simulation of RPBs. The predicted liquid holdup distribution agrees very well with experimental data. The new porous media model is the most accurate among current investigated models. Abstract: The rotating packed bed (RPB) is a promising advanced reactor used in industrial gas-liquid two-phase reaction processes because of its high phase contact efficiency and mixing efficiency. Investigation of RPBs using CFD simulations will improve the understanding of physical behaviours of gas and liquid flows in such reactors. Currently, CFD simulations on the RPBs only focus on the volume of fluid (VOF) method. However, the VOF method is not suitable for simulations of pilot-scale 2D and 3D RPBs due to the limitations in computer resources, while the Eulerian method using a porous media model is a promising alternative method but it is rarely reported. The reason is that there are no suitable porous media models that accurately describe the drag force between the gas and liquid, the gas and solids and the liquid and solids due to the high porosity and the stacked wire screen packing used in RPBs. Therefore, the purpose of this paper is to propose a new model for modelling RPBs. The new proposed model is based on the Kołodziej high porosity wire screen one-phase porous media model. In this work, two experimental counter-current gas–liquid flow cases from the literatures have been used for validating the CFD simulation results. Finally, the new model has been compared with the current porous media models for traditional spherical or structured slit packed beds, which are the Attou, Lappalainen, Iliuta and Zhang models. The simulation results show that the proposed new model is the most appropriate and accurate model for the simulation of RPBs among all the models investigated in this paper.